Proceedings of The 8th Romanian National HIV/AIDS Congress and The 3rd Central European HIV Forum. Issue 3 (June 2016) - Alexiev, Ivailo; Dimitrova, Reneta; Gancheva, Anna; Kostadinova, Asya; Stoycheva, Mariyana; Nikolova, Daniela; Elenkov, Ivaylo; Tilișcan, Cătălin; Predescu, Mioara; Păunescu, Bogdan; Streinu-Cercel, Anca; Săndulescu, Oana; et al.
Abstract O1 HIV-1 diversity in Bulgaria (current molecular epidemiological picture) Ivailo Alexiev, Reneta Dimitrova, Anna Gancheva, Asya Kostadinova, Mariyana Stoycheva, Daniela Nikolova, Ivaylo Elenkov O2 Knowledge, attitudes and practices of the general population on HIV/AIDS, hepatitis B and C in Romania Cătălin Tilișcan, Mioara Predescu, Bogdan Păunescu, Anca Streinu-Cercel, Oana Săndulescu, Claudiu Mihai Șchiopu, Mădălina Hristache, Lăcrămioara Aurelia Brîndușe, Adrian Streinu-Cercel O3 The prevalence of human leukocyte antigen-B*57:01 allele carriers and CXCR4 tropism among newly diagnosed HIV infected patients in Serbia Marija Todorovic, Marina Siljic, Dubravka Salemovic, Valentina Nikolic, Ivana Pesic-Pavlovic, Jovan Ranin, Djordje Jevtovic, Maja Stanojevic O4 HIV transmission among stable serodiscordant couples from the former Pediatric Cohort follow up in the National Institute of Infectious Diseases Ana Maria Tudor, Delia Vlad, Mariana Mărdărescu, Sorin Petrea, Cristina Petre, Ruxandra Neagu-Drăghicenoiu, Rodica Ungurianu, Alina Cibea, Odette Chirilă, Cristian Anghelina, Ileana Coserea O5 Unemployment is associated with syringe sharing among people who inject drugs in Greece Pantelia-Amalia Krikelli, Eirini Pavlitina, Mina Psichogiou, Demetris Lamnisos, Leslie Williams, Anya Korobchuk, Britt Skaathun, Pavlo Smyrnov, John Schneider, Vana Sypsa, Dimitrios Paraskevis, Angelos Hatzakis, Samuel R. Friedman, Georgios K. Nikolopoulos O6 Correlation of adipocytokine levels in different types of lipodystrophy in HIV/AIDS patients Gordana Dragović, Danica Srdić, Al Musalhi Khawla, Ivan Soldatović, Jelena Nikolić, Djordje Jevtović, Devaki Nair O7 IP10 – a possible biomarker for the progression of HIV infection Aura Temereanca, Adelina Rosca, Luminita Ene, Benchawa Soontornniyomkij, Carmen Diaconu, Claudia Dita, Cristian Achim, Simona Ruta O8 A permanent challenge: persistent low viremia in HIV positive patients on ART Șerban Benea, Ruxandra Moroti, Raluca Jipa, Eliza Manea, Andrada Stan, Elisabeta Benea, Dan Oțelea, Adriana Hristea O9 Infections in IDUs according to their HIV status Adriana Hristea, Irina Lăpădat, Raluca Jipa, Ruxandra Moroti, Șerban Benea, Doina Antonică, Irina Panait, Roxana Petre O10 Trends in combined antiretroviral therapy used in methadone program integrated with HIV care - 20 years of experience Justyna D. Kowalska, Ewa Pietraszkiewicz, Ewa Grycner, Ewa Firlag-Burkacka, Andrzej Horban O11 Extracellular cyclophilin A – inflammatory mediator in HIV infected patients Ovidiu Vlaicu, Leontina Bănică, Simona Paraschiv, Ana-Maria Tudor, Ruxandra Moroti, Dan Oțelea O12 High cardiovascular disease risk in Serbian population, an issue of concern Bojana Dimitrijević, Ivan Soldatović, Đorđe Jevtović, Jovana Kusić, Dubravka Salemović, Jovan Ranin, Gordana Dragović O13 Genotypic rifampicin resistance in HIV/ tuberculosis coinfected patients from a tertiary level infectious diseases hospital Dragoș Florea, Ioana Bădicuț, Alexandru Rafila, Cornel Camburu, Adriana Histrea, Mihaela Frățilă, Dan Oțelea O14 Occurrence of residual HCV RNA in liver and peripheral blood mononuclear cells among patients with chronic hepatitis C infection and/or HCV/HIV coinfection after IFN-based therapy Ivana Gmizic, Dubravka Salemovic, Ivana Pesic-Pavlovic, Marina Siljic, Valentina Nikolic, Miljana Djonin-Nenezic, Ivana Milosevic, Branko Brmbolic, Maja Stanojevic O15 Romanian nationwide screening for infection with HIV and hepatitis B and C viruses Anca Streinu-Cercel, Oana Săndulescu, Alina Cristina Neguț, Mioara Predescu, Alexandra Mărdărescu, Mihai Săndulescu, Adrian Streinu-Cercel O16 Treatment emergent variants to combined direct antiviral agents therapy against hepatitis C virus Ana Belen Pérez, Natalia Chueca, Marta Álvarez, Juan Carlos Alados, Antonio Rivero, Francisco Vera, Marcial Delgado, Javier Salmeron, Miguel Jiménez, Maria José Blanco, Moises Diago, Miguel Garcia-deltoro, Marta Alvarez, Francisco Téllez, Federico García O17 Clinical and epidemiological aspects in tuberculosis/HIV coinfected patients Diana Tănase, Eliza Manea, Rodica Bacruban, Dragoș Florea, Dan Oțelea, Alexandru Rafila, Mariana Mărdărescu, Adriana Hristea O18 Resistance to NS3 protease inhibitors in persons with chronic hepatitis C infected with hepatitis C virus subtype 1a from Croatia Ivana Grgic, Ana Planinic, Maja Santak, Lana Gorenec, Snjezana Zidovec Lepej, Adriana Vince O19 Analysis of a simplified diagnostic score for tuberculous meningitis in HIV-infected adults with meningitis Eliza Manea, Adriana Hristea, Șerban Benea, Ruxandra Moroti, Diana Tănase, Cristian M. Niculae, Simona Merisor, Raluca Jipa O20 Molecular tracing of the origin of HIV-1 infection among persons who inject drugs in Athens: a phyloethnic study Dimitrios Paraskevis, Evangelia Kostaki, Georgios K. Nikolopoulos, Vana Sypsa, Mina Psichogiou, Dimitra Paraskeva, Athanassios Skoutelis, Meni Malliori, Samuel R. Friedman, Angelos Hatzakis O21 The dynamics of virological response to HIV-1 infection and antiretroviral therapy initiation in patients with and without HLA-B*5701 Allele Malgorzata Hackiewicz, Piotr Zabek, Ewa Firlag-Burkacka, Andrzej Horban, Justyna Dominika Kowalska O22 Increase in the numbers of non-B subtypes and potential recombinant forms circulating among Slovenian MSM in the recent years Maja M. Lunar, Jana Mlakar, Mario Poljak O23 Genotyping intrahost polymorphisms in hepatitis C virus E2 protein associated with resistance to antibody neutralization Leontina Bănică, Eliza Martin, Valeriu Gheorghiță, Andrei Petrescu, Dan Oțelea, Costin-Ioan Popescu, Simona Paraschiv O24 Genotyping of HCV NS3 protease inhibitors resistance and phenotyping of rare double resistance mutations in HCV cell culture system Emil Neaga, Vlaicu Ovidiu, Andrei Juncu, Leontina Bănică, Simona Paraschiv, Dan Oțelea, Costin-Ioan Popescu O25 Employment status controls the relationship between neurocognitive impairment and depression in a cohort of young HIV-infected adults since childhood Adrian Luca, Florin Lazăr, Anca Elena Luca, Luminița Ene, Cristian Achim O26 Predictors of survival in parenterally-infected HIV positive children and youth diagnosed with progressive multifocal leukoencephalopathy Cosmina Gingăraş, Ștefan Adrian Anton, Roxana Rădoi, Simona Tetradov, Grațiela Țârdei, Maria Nica, Razvan Alexandru Capşa, Cristian L. Achim, Cristiana Oprea, Luminița Ene O27 Neurocognitive and brain functioning in HIV-infected young MSM treated with cART Bogna Szymańska, Natalia Gawron, Agnieszka Pluta, Emilia Łojek, Ewa Firląg – Burkacka, Andrzej Horban, Robert Bornstein, et HARMONIA3 Study Group O28 Clinical value of RT-PCR detection ofToxoplasma gondii DNA in cerebrospinal fluid Olivia Burcoș, Simona Manuela Erscoiu, Filofteia Bănicioiu Cojanu, Andreea Toderan, Maria Nica, Ionuț Cristian Popa, Emanoil Ceaușu, Petre Iacob Calistru O29 Characteristics of sleep disorders in Romanian adults infected with human immunodeficiency virus Manuela Arbune, Mirela Alexandrache, Anca-Adriana Arbune, Doina-Carina Voinescu O30 Diagnosing neuroHIV: the rift between clinicians and pathologists Ioan-Alexandru Diaconu, Laurențiu Stratan, Victoria Aramă, Luciana Nichita, Alexandra Diaconu, Anca Negru, Alina Orfanu, Anca Leuștean, Daniela Adriana Ion O31 A challenging neurological complication in a HIV-infected young woman with multiple opportunistic infections Irina Ianache, Cristiana Oprea O32 Brain abscess with uncertain etiology in a late-presenter HIV infected patient Anca Leuștean, Cristina Popescu, Alina Orfanu, Anca Negru, Remulus Catana, Cristina Murariu, Ioan-Alexandru Diaconu, Mihaela Rădulescu, Cătălin Tilișcan, Victoria Aramă O33 Cerebral toxoplasmosis and left crural monoparesis with fatal evolution in a noncompliant patient with AIDS C3 Iosif Marincu, Patricia Poptelecan, Valeria Bică, Florin Lazăr, Livius Tirnea O34 Opportunistic infections still a problem in HIV-infected patients in cART era: a Romanian single center experience Irina Ianache, Roxana Rădoi, Manuela Nica, Grațiela Țârdei, Luminița Ene, Emanoil Ceaușu, Petre Calistru, Cristiana Oprea P1: Epidemiological aspects of co-infection of HIV/TB in Moldova Iurie Osoianu, Ala Halacu P2 Perinatal exposure at HIV infection in Oltenia region Andreea Cristina Stoian, Florentina Dumitrescu, Iulian Diaconescu, Augustin Cupșa, Lucian Giubelan, Loredana Ionescu, Irina Niculescu P3 Women living with HIV in Mureș county Carmen Chiriac, Nina Șincu, Iringo Zaharia Kezdi, Anca Georgescu, Brândușa Țilea, Cristina Girbovan, Andrea Incze, Andrea Fodor P4 Late diagnosis of HIV infection in children - a challenge for Romania Alina Cibea, Mariana Mărdărescu, Cristina Petre, Ruxandra Drăghicenoiu, Rodica Ungurianu, Ana Maria Tudor, Delia Vlad, Carina Matei P5 Cirrhosis Assessment in Patients Co-infected HIV-Hepatitis B Virus Elena Dumea, Lucian Cristian Petcu, Simona Claudia Cambrea P6 HIV late presenters in Craiova Regional Center, Romania Florentina Dumitrescu, Augustin Cupsa, Andreea Cristina Stoian, Lucian Giubelan, Irina Niculescu, Iulian Diaconescu, Dan Hurezeanu, Livia Dragonu, Mioara Cotulbea P7 Some aspects of malignancies in patients HIV / AIDS Simona Manuela Erscoiu, Ionuț Cristian Popa, Denisa Stroie, Petronela Ionescu, Nedeea Duță, Camelia Dobrea, Irina Voican, Emanoil Ceaușu, Petre Iacob Calistru P8 Factors associated with resilience among people living with HIV in Romania Florin Lazăr P9 Fever in HIV-infected patients: a thorny problem to be solved by the clinicians Lucian Giubelan, Augustin Cupșa, Iulian Diaconescu, Florentina Dumitrescu, Dan Hurezeanu, Livia Dragonu, Irina Niculescu, Andreea Cristina Stoian, Oana Obretin, Mariana Stănescu, Mihai Jianu P10 Th1, Th2, Th9, Th17 and Th22 cytokines in acute and chronic HIV-1 infection Lana Gorenec, Snjezana Zidovec Lepej, Ivana Grgic, Ana Planinic, Janja Iscic Bes, Adriana Vince, Josip Begovac P11 Dyslipidemia in HIV-infected patients treated with protease inhibitors – case report Luminița Elena Horga P12 Why use less treatment for the metabolic abnormalities in HIV patients-too many drugs? Corina Itu, Luminița Elena Horga, Laura Augusta David-Aldea, Anca Ciorogar, Cristian Jianu, Mihaela Lupșe P13 Sacral Herpes Zoster, with hyperalgesic form, in a patient with C3 stage HIV infection Iuliana Caramangiu, Ovidiu Roșca, Monica Cialma, Andreea Ardeleanu, Iosif Marincu P14 Factors associated with in-hospital mortality in tuberculous and cryptococcal meningitis Raluca Jipa, Eliza Manea, Șerban Benea, Irina Lăpădat, Nicoleta Irimescu, Irina Panait, Cristian Niculae, Adriana Hristea P15 Lipodystrophy: still present adverse event in resource-limited settings Jovana Kusic, Djordje Jevtovic, Dubravka Salemovic, Jovan Ranin, Bozana Dimitrijevic, Gordana Dragovic P16 TB and HIV coinfected patient, an emergent challenge - case report Laura-Augusta Aldea-David P17 Efficacy of prophylactic antiretroviral treatment in new-born infants from HIV-positive mothers in 2012-2014, for the North-Eastern part of Romania Carmen Manciuc, Cristina Nicolau, Liviu Prisăcariu, Alexandra Largu P18 Surveillance of mother to child transmission of HIV in Romania – 31 December 2015 Mariana Mărdărescu, Adrian Streinu-Cercel, Cristina Petre, Marieta Iancu, Sanda Vintilă, Daniela Vitelaru, Iosif Ionel, Claudiu Mihai Șchiopu, Alexandra-Henriette Mărdărescu P19 The antiretroviral therapy failure and the need to select the effective treatment in the Republic of Moldova Pavel Micsanschi, Tiberiu Holban, Ina Bîstrițchi, Lucia Pârțână, Angela Nagîț, Svetlana Popovici, Maria Talmaci, Irina Cucerova P20 Disseminated cryptococcosis in a patient with C3 HIV stage and multiresistant to antiretroviral therapy with lethal evolution Sorina Georgiana Mitrescu, Dana Mihalcea, Iulia Caramangiu, Ovidiu Roșca, Iosif Maricu P21 Aspects of tuberculosis infection in HIV-positive patients from Romania – our experience Anca Negru, Daniela Munteanu, Victoria Aramă, Raluca Mihăilescu, Ioan Diaconu, Remulus Catana, Cristina Popescu, Alina Orfanu, Anca Leuștean, Mihaela Rădulescu, Cătălin Tilișcan, Raluca Năstase, Violeta Molagic, Irina Duport, Cristina Dragomirescu, Ștefan Sorin Aramă P22 Dyslipidemia in HIV-infected patients Nicoleta M Negruț P23 Challenges in the management of an HIV seropositive patient with psoriasis undergoing immunomodulator therapy Violeta Elena Niță, Daniela Ioana Munteanu, Raluca Mihăilescu, Ioan Diaconu, Anca Negru, Cristina Popescu, Victoria Aramă P24 Acute peritonitis as a sign of IRIS in an HIV-infected patient with MAC latent infection Alina Orfanu, Cristina Popescu, Anca Leuștean, Anca Negru, Remulus Catana, Ioan Diaconu, Cătălin Tilișcan, Victoria Aramă, Sorin Ștefan Aramă P25 The virologic outcome of the treatment of chronic hepatitis B among HIV co-infected patients on HAART Ivana Pesic Pavlovia, Dubravka Salemovic, Jovan Ranin, Djordje Jevtovic P26 A case of HIV encephalopathy with aphasia, agnosia, apraxia and right homonymous hemianopsia Ovidiu Roșca, Andreea Ardeleanu, Iulia Caramangiu, Daniela Desaga, Valerica Bică, Sorina Mitrescu, Iosif Marincu P27 Molecular footprints on human immunodeficiency virus -1 genome and association with phylogenetic clustering among subtype B infected patients in Serbia Marina Siljic, Dubravka Salemovic, Valentina Nikolic, Djordje Jevtovic, Ivana Pesic-Pavlovic, Jovan Ranin, Marija Todorovic, Maja Stanojevic P28 Neurosyphilis and human immunodeficiency virus infection: double challenge Nina-Ioana Șincu, Anca Georgescu, Brândușa Țilea, Iringo Zaharia Kezdi, Andrea Incze, Cristina Gârbovan, Carmen Lucia Chiriac P29 Differences between HIV-infected adults since childhood and non HIV-infected persons on managing everyday life Anca Elena Luca, Florin Lazăr, Adrian Luca, Luminița Ene, Roxana Rădoi, Adina Talnariu, Silvia Suciu, Cristian Achim P30 Molecular detection ofBartonella quintana in a HIV immunodepressed patient with fever and isolated lymphadenopathy - Case report Diana Gabriela Iacob, Dragoș Florea, Simona Iacob P31 Present epidemiological characteristics of HIV/AIDS newly diagnosed cases in South-Eastern Romania Manuela Arbune, Miruna Drăgănescu, Alina Iancu P32 The gender's preferences among opportunists? Ruxandra Moroti, Cristian M Niculae, Simona Merisor, Eliza Manea, Serban Benea, Andrada Stan, Raluca Hrisca, Raluca Jipa, Diana Tanase, Adriana Hristea P33 Polymorphism of interleukin-28B gene in persons with chronic hepatitis C from Croatia Ivana Grgic, Ana Planinic, Lana Gorenec, Snjezana Zidovec Lepej, Adriana Vince